Location choices of highly-educated foreign workers: the importance of urban amenities - Or Levkovich; Jan Rouwendal (European Regional Science Association (ERSA), 2014)
Current developed economies' growth becomes increasingly dependent on the performance of innovation and skill-intensive industries. Therefore, the ability of cities to attract skilled or highly-educated individuals becomes more and more important for their growth and economic development. In this research we estimate a residential sorting model in order to shed light on the factors that determine the location choices of foreign skilled workers. We do so by estimating their valuation of various urban amenities in the municipalities of the densely populated Randstad area in the west of the Netherlands, and investigating which amenities increase the attractiveness of these municipalities. We also consider heterogeneity in individual preferences, and compare housing preferences and marginal willingness to pay for amenities between groups based on skill levels and origin. We find that job opportunities, accessibility, natural amenities and presence of historic monuments and buildings are highly valued by both domestic and migrants with high-education. Our results also provide evidence that social amenities, such as an existing community of migrants in a municipality, have an important role in determining the attractiveness of a location.
Keywords: J61; R11; R21; R23; 330